PELATIHAN MENGGUNAKAN MEDIA PEMBELAJARAN BAHASA BAGI GURU MADRASAH IBTIDAIYAH DI DESA SIDODADI RAMUNIA, KECAMATAN BERINGIN - Imelda Darmayanti Manurung; Yusriati; Selamat Husni Hasibuan (Journal of Science and Social Development, 2019)
The Community Partnership Program aims to improve the skills of using language learning media for Madrasah ibtidaiyah teachers in MIS Al-Ikhlas Sidodadi Ramunia and MIS TPI Al-Fajar. This is based on the madrasah ibtidaiyah teaching curriculum, where students are taught in addition to Indonesian subjects, also taught Arabic as the main subject, and English as an additional subject. Thus, a class teacher at the Islamic school must be able to master and teach the three languages to students properly and correctly in accordance with the specified competencies. However, the lack of knowledge, abilities, and skills of Madrasah Ibtidaiyah teachers in using learning media in teaching languages, especially foreign languages, as well as the different levels of mastery of the abilities and skills of classroom teachers in Islamic schools in teaching these three languages caused a lack of interest and motivation in learning. language in students. This results in low mastery of students' language skills, especially Arabic and English. To solve this problem, the provision of training and mentoring skills in the use of language learning media adapted to integrated language teaching material to madrasah ibtidaiyah classroom teachers is expected to improve students' language knowledge at the same level. The results achieved from this activity are the increase in knowledge, abilities, and skills of Madrasah Ibtidaiyah teachers in conducting language teaching and learning activities using appropriate language learning media.